Tumor Burden Score Stratifies Prognosis of Patients With Intrahepatic Cholangiocarcinoma After Hepatic Resection: A Retrospective, Multi-Institutional Study - Li, Hui; Liu, Rongqiang; Qiu, Haizhou; Huang, Yang; Liu, Wenbin; Li, Jiaxin; Wu, Hong; Wang, Genshu; Li, Dewei (Frontiers in Oncology, 2022)
Background The prognostic significance of tumor burden score (TBS) on patients who underwent curative-intent resection of intrahepatic cholangiocarcinoma (ICC) has not been evaluated. The present study aimed to investigate the impact of TBS and its synergistic effect with CA19-9 (combination of TBS and CA19-9, CTC grade) on long-term outcomes. Methods Patients who underwent radical resection of ICC between 2009 and 2017 were retrospectively identified from a multi-center database. The overall survival (OS) and recurrence-free survival (RFS) were examined in relation to TBS, serum preoperative CA19-9, and CTC grade. Results A total of 650 patients were included in our study (509 in the derivation cohort and 141 in the validation cohort). Kaplan–Meier curves showed that both TBS and CA19-9 levels were strong predictors of survival outcomes. Patients with elevated TBS grade or elevated CA19-9 were associated with worse OS and RFS (both p < 0.001). As expected, CTC grade also performed well in predicting long-term outcomes. Patients with low TBS/low CA19-9 (CTC grade 1) were associated with the best OS as well as RFS, while high TBS/high CA19-9 (CTC grade 3) correlated to the worst outcomes. In the validation cohort, TBS grade, preoperative CA19-9, and CTC grade also stratified prognosis among patients (p < 0.001 for each). Conclusions Both tumor morphology (tumor burden) and tumor-specific biomarker (serum CA19-9) were important when evaluating prognosis of patients with resectable ICC. Serum CA19-9 and TBS showed a synergistic effect on prognostic evaluation. CTC grade was a promising tool in stratifying prognosis of ICC patients after curative resection.